Understanding the socio‐technical hybridisation of indoor–outdoor relations: Emergent, merged, and stretched. Issue 4 (6th May 2021) - Marvin, Simon; Rutherford, Jonathan
Abstract: Indoor and outdoor leisure environments are increasingly understood to be mutually constituted through merged relationships but there has been less focus on the actual forms that hybridisation can take. This paper provides an analysis of forms of hybridisation through time by focusing on the socio‐technical configurations through which three leisure environments are materially constituted. We analyse the key functional elements of these configurations: the technological systems and their genealogies over time that allow the making and unmaking of activities; the spatiality of facilities and systems in terms of their locations and connections across space; and the construction by providers of user pathways between indoor and outdoor activities. The paper uses this structure to compare purpose‐built indoor recreational spaces located in the city region of Greater Manchester that recreate outdoor activities focusing on skydiving, skiing, and ice wall climbing. We construct a framework of three modes of hybridisation – emergent, merged, stretched – that contributes a deeper understanding of the diversity, intensity, and changing temporality of interrelations between indoor and outdoor environments. Abstract : The paper compares purpose‐built indoor recreational spaces located in the city region of Greater Manchester that recreate outdoor activities of skydiving, skiing, and ice wall climbing. We construct a framework of three modes of hybridisation – emergent, merged, stretched – that contributes a deeper understanding of the diversity, intensity, and changing temporality of interrelations between indoor and outdoor environments.